The Influence of Financial Education, Inflation, and Per Capita Expenditure on the Intermediation Function of Rural Banks (BPR) in Indonesia - Putra, Rino Dwi; Raga, Ridha Azka; Hayati, Dian Indah (Universitas Negeri Padang, 2025)
Abstract Purpose –This study examines the impact of financial education, inflation, and per capita expenditure on the intermediation function of Rural Banks (BPR) in Indonesia, focusing on deposit mobilization and credit distribution across all provinces in 2024. The research is grounded in the accounting and financial management perspective, recognizing that intermediation outcomes are not only reflective of market behavior but also integral to financial reporting, institutional performance measurement, and regional economic accountability. Disparities in financial literacy and regional economic indicators have implications for the effectiveness of BPRs, which serve as key financial intermediaries for local communities and MSMEs. Design/methodology/approach –Using cross-sectional data from 34 provinces in Indonesia in 2024, this research applies Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the relationships between financial literacy, macroeconomic indicators, and BPR intermediation performance. Findings –This study identifies that financial education significantly influences deposit mobilization, indicating its role in shaping public trust and engagement in financial institutions. However, it does not significantly affect credit distribution. Inflation shows no effect on deposit mobilization but significantly impacts credit allocation, suggesting sensitivity in credit risk assessments and lending decisions. Per capita expenditure also demonstrates a significant effect on credit distribution, highlighting the relevance of consumption-based financial behavior in credit demand forecasting. Originality/value – From an accounting standpoint, these findings underscore the importance of integrating non-financial indicators such as education and macroeconomic variables into performance evaluation frameworks for BPRs. Strengthening financial education initiatives could improve deposit liabilities reported in BPR financial statements, while inflation and consumption trends should be factored into provisioning and credit risk disclosures. The results have practical implications for regulatory bodies, financial educators, and BPR management in aligning financial intermediation strategies with sound accounting practices and sustainable local economic development Research limitations/implications –The use of cross-sectional data limits the ability to capture temporal dynamics. Future research should consider panel data and additional macroeconomic or seasonal factors to enrich the analysisKeywords: financial literacy, inflation, rural banks, credit distribution, deposit mobilization